Jaminan Kepentingan rakyat dan Pelaksanaan Otonomi Daerah - Yusdani Yusdani (Millah: Journal of Religious Studies, 2001)
The political decision of government of the decentralization policy through the Act No. 22,1999, is one of the fundamental political decision. The implications of the decision give vast impact on territories and the central government. Generally, all of the society components accept with pleasure the decision because it is the democracy gate for the democracy on all of aspects. This era is described as the economical democracy era. The resource of territory will be used optimally by the people. From this is where the economics distribution is going to move.